1989
DOI: 10.1002/ijc.2910440433
|View full text |Cite
|
Sign up to set email alerts
|

In vitro infection of cell lines with HTLV‐I and SIVmac results in altered intracellular free calcium concentration and increased membrane polarization

Abstract: This study was designed to determine whether retrovirus infection alters basal concentrations of intracellular free calcium, the magnitude of intracellular free calcium change upon receptor-mediated cell-stimulation, and cell membrane polarization. Two retrovirus-infected cell lines were utilized: HTLV-I-infected MT-2 cells and SIV-infected H-9 cells. Uninfected H-9 cells were used as controls. The results show that the retrovirally-infected cells had an increased basal concentration of intracellular free calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…H9-infected cells, as well as T cells from the peripheral blood of SS patients, were defective in their ability to generate a rise in [Ca"], following stimulation. Similar observations have been reported with HIV-l-infected T cells (8,27), as well as with HTLV-1-and simian immunodeficiency virus ( S I V t infected T cells (28,29). While H9-infected cells had decreased basal concentrations of intracellular free calcium, HIV-1 (8), HTLV-I (28), and SIV-infected (28) cells had increased basal levels of intracellular free calcium.…”
Section: Discussionsupporting
confidence: 84%
“…H9-infected cells, as well as T cells from the peripheral blood of SS patients, were defective in their ability to generate a rise in [Ca"], following stimulation. Similar observations have been reported with HIV-l-infected T cells (8,27), as well as with HTLV-1-and simian immunodeficiency virus ( S I V t infected T cells (28,29). While H9-infected cells had decreased basal concentrations of intracellular free calcium, HIV-1 (8), HTLV-I (28), and SIV-infected (28) cells had increased basal levels of intracellular free calcium.…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies have shown that upon activation of the inflammatory response, the production of ROS increases, causing damage to the blood-brain barrier (BBB) and mitophagy activation, together with elevated expression of inflammatory cytokines [89,90,91,92]. Mitochondrial calcium homeostasis is reported to be disrupted in infectious diseases, indicating that mitochondrial calcium may be involved in inflammation-associated diseases (Figure 2) [93,94,95,96]. To date, evidence has indicated that the MCU plays an important role in the regulation of bacteria- and virus-induced activation of inflammation.…”
Section: The Function Of the Mcu In Inflammationmentioning
confidence: 99%